RESPONSIBILITY OF SERVICE TO INPATIENTS AT NEGERI LAMA PUBLIC HEALTH CENTER, SUB-DISTRICT DOWNSTREAM BAR - Intan Nasution; Muklir; Aflia Riski; Muhammad Hasyem; Teuku Alfiady (RADJA PUBLIKA, 2025)
Responsiveness is one of the important indicators in public services that reflects the ability and alertness of the apparatus or officers in responding to the needs, complaints, and expectations of the community as service users. This study aims to determine the responsiveness of services to inpatients at the Lama Public Health Center, Bilah Hilir District and to find out what obstacles are faced by inpatients at the Lama Public Health Center. This study was motivated by the many complaints from the community regarding slow services, unfriendly attitudes of officers, and the service process that takes quite a long time. The focus of this study discusses the responsiveness of services to inpatients at the Lama Public Health Center, Bilah Hilir District, which includes aspects of responding, speed and accuracy of service, and discussing the inhibiting factors that occur in the service process for inpatients at the Lama Public Health Center. The method used in this study is descriptive qualitative. Data collection techniques are carried out through in-depth interviews, direct observation, and documentation. The results of the study indicate that the services provided by the Lama Public Health Center are still not fully responsive to patient needs. There are several major obstacles, such as limited medical personnel, ineffective manual queuing system, lack of training on excellent service, and the absence of a structured complaint system. These factors cause delays in service and reduce the level of public satisfaction. Responsiveness indicators such as speed, accuracy, and the ability of officers to respond to complaints have not been optimally met. Therefore, it is necessary to make comprehensive improvements to the Puskesmas service system. Suggestions from this study are the addition and equalization of medical personnel, digitization of service and administration systems, HR training in communication and service ethics, optimization of triage systems and priority routes, improvement of medical facilities and infrastructure, especially in first-level service facilities such as Puskesmas.